Exploring the Dynamics of Government Hospital Internal Audit: A Transcendental Phenomenological Study - Prayudi, Made Aristia; Mursito, Kendhy; Adnyana, I Dewa Gede Anom Jambe (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This research explores the supervisory experiences of the Internal Audit Unit (IAU) team at an Indonesian government hospital. Design/Methodology/Approach: This study employs a qualitative research approach with an interpretive paradigm and Husserl's transcendental phenomenological design. The informants consist of the chair, secretary, and a member of the IAU team at a government hospital in Bali Province. Research findings: The IAU team in a government hospital experiences marginalization, role ambiguity, and covert resistance from managerial and clinical units, which undermines their supervisory efforts. Despite structural and cultural barriers, the IAU team maintains professional integrity and continues to perform administrative, consultative, and supervisory roles under constrained authority. Their experiences highlight emotional labor and the struggle for strategic recognition within a complex healthcare governance structure. Theoretical contribution/Originality: This study reinforces Husserl's transcendental phenomenology in uncovering institutional tensions between clinical autonomy and administrative control. The study offers a unique application of transcendental phenomenology to internal audit functions in Indonesian public hospitals, revealing deep-seated role tensions rarely explored in existing healthcare governance literature. Practitioner/Policy implication: Practically, empowering internal auditors with more explicit mandates and fostering collaborative cultures can enhance hospital governance and accountability. Research limitation/Implication: The study is limited by challenges in accessing and scheduling informants within a hospital setting, which may have restricted the depth of some narratives; however, the findings underscore the need for stronger institutional support to enhance the role and effectiveness of internal auditors in public healthcare governance.